Socio-Economic Development through Regional Organizations: A Study of the Implementation of Agenda 2063 by the African Union (AU) in Collaboration with China - Muhammad Amjad Raza; Dr. Abdul Basit Khan (Annals of Human and Social Sciences, 2024)
The African Union (AU) unveiled Agenda 2063 in 2013 which is a strategic framework that sets sights on wide-ranging growth, international collaborations and sustainable development, with a special focus on infrastructure development. While aligning the objectives of the Belt & Road Initiative (BRI) with those of Agenda 2063, China has also emerged as a key stakeholder in the economic wellbeing of the African continent. The instant study explores the evolving role and status of the AU with special reference to its collaboration with China in terms of socio-economic development of the continent by examining key areas of this partnership with respect to the implementation of Agenda 2063, the impact of these interactions on Africa's development, and the challenges and opportunities that lie ahead of the parties involved. By analysing the AU's strategies and initiatives in engaging with China, the study provides a comprehensive understanding of the dynamics at play in this crucial partnership and the potential pathways for enhancing Africa's global standing through effective regional diplomacy and cooperation. It qualitatively analyses the official reports, statements, literature and public records and finds that the AU has proved quite influential and successful forum for the transformation of this “hopeless continent” into a hopeful region for its inhabitants, nevertheless, this vigilance and activism shuld be kept alive until the attainment of all the desired goals.
Keywords: Agenda 2063; Belt & Road Initiative (BRI); China-African Union (AU) Relations